Unveiling the Untold Story of Food Security Level in Indonesia’s Households with Disabilities - Sritutur, Fera Febriana; Rahman, Abdur (Indonesian Journal of Disability Studies, 2025)
One of the objectives of the Sustainable Development Goals (SDGs) is to eradicate hunger and achieve global food security. People with disabilities are often confronted with socioeconomic challenges, stemming from their inability to access fundamental services and opportunities. This is largely due to their disability, which can impede their ability to participate fully in the workforce and generate income. Their condition limits access to sufficient food. This study aims to analyze the food security level of households with disabilities in Indonesia using SUSENAS data. To this end, we have employed a cross-tabulation analysis to address the research question. The study’s findings reveal that a significant proportion of households with disabilities in Indonesia are food insecure, characterized by food vulnerability, insufficient food intake, and food insecurity. This findings underscores the heightened vulnerability of households with disabilities in Indonesia to food insecurity, a phenomenon that is further compounded by their diverse socio-demographic characteristics. The Indonesian government must develop policies that specifically target people with disabilities and increase their access to sufficient food and existing opportunities.